Utilization of Waste Materials for Rearing the Small Carpenter bee, Ceratina (Pithitis) smaragdula F. (Hymenoptera, Apidae) - ABROL, DHARAM PAL (ENTOMOLOGIA HELLENICA, 2025)
Ceratina (Pithitis) smaragdula is a recognized pollinator of alfalfa and various other crops. Artificial nesting of the species will aid its conservation and enhance its pollination services to the agroecosystems. Hollow waste stems of Saccharum spp., which are typically discarded as waste, were tested as nesting material for C. smaragdula and found to be highly beneficial for enhancing and maintaining these insect-pollinators in the agroecosystems.